Industrial Training Report: Perpustakaan Tengku Anis UiTM Cawangan Kelantan / Nurul Nur Fatihah Shapie - Shapie, Nurul Nur Fatihah (Tengku Anis Library Uitm Machang, 2022)
In this industrial training report, it provides a thorough description about the practical training which are being carried out at Perpustakaan Tengku Anis, UiTM Machang Kelantan for 5 months. There are 4 chapters contains introduction to UiTM Machang and Perpustakaan Tengku Anis, organizational structure from 4 departments and 9 units at Perpustakaan Tengku Anis, the whole activities that are being carried out during the practical traning and special project managed. Lastly, knowledge and lesson gained during the time period of traning. The first chapter of the report is an introduction to the background of UiTM Machang and Perpustakaan Tengku Anis. Proceed to the next chapter, show thorough organizational structure with details explanation of departments and units in PTA such as administration, customer service. Third chapter was about training activities performed during training period followed by last chapter that conclude the report with all points of knowledge and lesson learned as the outcomes if industrial training.